2009
DOI: 10.1590/s0100-69912009000600004
|View full text |Cite
|
Sign up to set email alerts
|

Trauma torácico: análise de 124 pacientes submetidos à toracotomia

Abstract: Methods Methods Methods Methods: We performed a retrospective study through analyzed records in the two main reference hospitals for trauma adults in this city during a period of 5 years. We considered for this study the epidemiological data, causal agent, type of incision, anatomical classification score of trauma, prognostic factors and mortality. Results Results ResultsResults Results: We analyzed 124 patients who underwent thoracotomy with a mean age of 28 years. Stab wounds were the most common casual age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
(11 reference statements)
1
3
0
8
Order By: Relevance
“…Studies which analyze survivors of cardiac trauma in hospital cases are frequent in literature [14][15][16][17][18] . In our review, we showed that the majority of deaths occurred in men, with median age of 27 years, a similar result as the ones shown in studies performed both in Latin America 14,[21][22][23] and in the United States 3,24,25 . GSW was the trauma mechanism in 62.3% of the deaths in our series.…”
Section: Methodssupporting
confidence: 87%
“…Studies which analyze survivors of cardiac trauma in hospital cases are frequent in literature [14][15][16][17][18] . In our review, we showed that the majority of deaths occurred in men, with median age of 27 years, a similar result as the ones shown in studies performed both in Latin America 14,[21][22][23] and in the United States 3,24,25 . GSW was the trauma mechanism in 62.3% of the deaths in our series.…”
Section: Methodssupporting
confidence: 87%
“…It is interesting to point out that among the 23 cases where operatory findings were classified as compatible with heart injury, in six patients there was hemopericadium, but no injury to any cardiac chamber or intrapericardial vessel was found (five cases went through pericardial window followed by thoracotomy, and in one case no pericardial window was performed). This finding of blood inside the pericardium, without detecting intrapericardial structure injury is described as a false positive result of the pericardial window, and this can happen in 18% to 30% of the cases 8,19 . According to the casuistry of the present study, this happened in 25% of the pericardial windows.…”
Section: Discussionmentioning
confidence: 99%
“…The right ventricle is often described as the most affected cardiac chamber in penetrating injuries, because it accounts for most of the anterior surface of the heart (sternocostal), with predominance ranging from 30% to 48% 3,8,13,[19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…De maneira geral o acesso em lesões ao lado direto do hemitórax são abordadas com a associação de uma esternotomia medial com incisão clavicular, enquanto do lado esquerdo a melhor abordagem é a toracotomia anterolateral em "livro aberto", que expõe completamente o arco aórtico e os grandes vasos. Nesta experiência foi optado pela toracotomia antero-lateral que possibilitou a visualização da lesão e controle proximal da transfixação da artéria axilar 2,6,10,11 . Há referências que demonstram que a utilização de esternotomia mediana é suficiente em ambos os lados, e que esse procedimento tem menor potencial mórbido sendo assim mais indicado (Figura 6).…”
Section: Discussionunclassified